Developing an AI-Assisted Visual Novel Game for Phase C IPAS History Learning - Agung Marhadi; M. Fachri Adnan; Muhammadi; Ulfia Rahmi; Istiqomah As Sayfullooh (Universitas Pendidikan Ganesha, 2025)
Learning IPAS, particularly history content in Phase C at the elementary school level, is still predominantly characterized by conventional, teacher-centered approaches with limited use of interactive media, resulting in suboptimal student engagement and learning experiences. At the same time, the development of game-based learning media often faces technical complexity and resource constraints. This study aims to develop and analyze the validity and practicality of an Artificial Intelligence (AI)-assisted visual novel history game as a learning medium for Phase C IPAS instruction. This research employed an Educational Design Research (EDR) approach using the Plomp & Nieveen model, which consists of three stages: preliminary research, prototype development, and assessment. The research subjects involved subject-matter experts, media experts, language experts, teachers, and elementary school students. Data were collected through interviews, observations, validation questionnaires, and practicality questionnaires. Data analysis was conducted using descriptive quantitative and qualitative techniques. The results indicate that the developed media demonstrates a very high level of validity based on evaluations by instructional, technical, and language experts, as well as a very good level of practicality based on responses from teachers and students. These findings suggest that the AI-assisted visual novel history game is feasible for use as an IPAS learning medium and has the potential to enhance student engagement, motivation, and meaningful interactive learning experiences. This study implies that integrating AI into the development of educational game media can serve as an innovative solution for improving IPAS instruction in elementary schools.